Students’ challenges on sustainable development (Training and Practice : Journal of Educational Sciences, 2020)
I examined the sustainability challenges responded to for the sake of saving our planet among young adult dormitory students. The results of the research support the hypothesis of how most students are sensitive to issues of sustainable development, i.e. they want to reduce their ecological footprint and have recognized that the development of sustainability depends not only on what they do, but also on how they act. The practical implementation of environmental awareness practices is realized through the activities of the three ‘guards’ of their immediate environment (recycling, waste reduction, recycling) as well as with their conscious shopping habits. I was able to examine their commitment to the topic by analysing their responses to my questionnaire.